Impatiens ramasubbuana, a new name for Impatiens palniensis Ramasubbu (Balsaminaceae) - Kottaimuthu, Ramalingam; Murugan, Perumal; Kumar, John Kennedy John Praveen; Basu, Muthuramalingam Jothi (Phytotaxa, 2021)
The genus Impatiens Linnaeus (1753: 937) contains a wealth of untapped treasures for gardeners and it is one of the mega diverse genera of angiosperms comprise about 1059 species (POWO 2020). According to the recent estimate, India is known to have 250 species and majority of them occur in Eastern Himalayas (Gogoi et al. 2018) and the Western Ghats (Bhaskar 2012). Tamil Nadu is one of the plant-rich states in the country and with 5674 angiosperm taxa, it ranks first among all the states in the country (Lakshminarasimhan et al. 2014).